2019
DOI: 10.3389/fmicb.2019.01811
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Straw Return Influences Nitrogen-Cycling and Pathogen Associated Soil Microbiota in a Wheat–Soybean Rotation System

Abstract: Returning straw to soil is an effective way to sustain or improve soil quality and crop yields. However, a robust understanding of the impact of straw return on the composition of the soil microbial communities under field conditions has remained elusive. In this study, we characterized the effects of wheat straw return on soil bacterial and fungal communities in a wheat–soybean rotation system over a 3-year period, using Illumina-based 16S rRNA, and internal transcribed region (ITS) amplicon sequencing. Wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 88 publications
4
41
1
Order By: Relevance
“…Furthermore, less aggressive species, such as Fusarium langsethiae and Fusarium poae, are also able to produce mycotoxin in infected hosts [58,59]. A study on fungal community dynamics in a wheat-soybean rotation system showed that incorporating wheat residues into the soil significantly reduced plant pathogen associated fungal taxa including, Fusarium and Alternaria in the soil at the early phrase of decomposition (0-60 days) [2]. In contrast, our results showed not only wheat pathogens Fusarium spp.…”
Section: Robustness Of Initial Fungal Wheat Residue Inhabitants To Mecontrasting
confidence: 50%
See 1 more Smart Citation
“…Furthermore, less aggressive species, such as Fusarium langsethiae and Fusarium poae, are also able to produce mycotoxin in infected hosts [58,59]. A study on fungal community dynamics in a wheat-soybean rotation system showed that incorporating wheat residues into the soil significantly reduced plant pathogen associated fungal taxa including, Fusarium and Alternaria in the soil at the early phrase of decomposition (0-60 days) [2]. In contrast, our results showed not only wheat pathogens Fusarium spp.…”
Section: Robustness Of Initial Fungal Wheat Residue Inhabitants To Mecontrasting
confidence: 50%
“…For example, the wheat pathogens Zymoseptoria tritici [10] and Oculimacula yallundae [11], colonize wheat residues and are able to infect the subsequent crop if the residues are left in the field after harvest. Hence, residue return can be considered to be a causative agent for plant diseases, by providing pathogen inoculum and suitable conditions for pathogen growth, propagation, and accumulation, which then results in epidemic diseases [2,7]. However, these complex microbial communities inhabiting plant residues have remained largely uncharacterized [12].…”
Section: Introductionmentioning
confidence: 99%
“…The application of biochar specifically enriched beneficial bacteria and decreased pathogen abundance ( Chen et al, 2020 ). Furthermore, Yang et al (2019) showed that wheat straw return significantly increased soil nitrogen and reduced the relative abundance of pathogenic fungal genera in the soil microbial community, indicating a potential for disease control. Thus, promoting the biocontrol effects of the soil microbial community against soil-dwelling pathogens by manipulating soil features is a promising strategy for soil-borne disease management.…”
Section: Interactions Of Microbial Communities With Plants and Soilmentioning
confidence: 99%
“…It has been widely accepted that microbial communities inhabiting soil are capable of alternating its physicochemical properties by organic litter deposition and metabolic activities ( Jacoby et al, 2017 ; Jansson and Hofmockel, 2020 ), for example, by improving water retention ( Naylor and Coleman-Derr, 2017 ), increasing carbon storage ( Jansson et al, 2018 ) and mineral nutrition contents ( van der Heijden et al, 2008 ; Jacoby et al, 2017 ). Vice versa, the variability in soil traits may impact the composition and function of soil microbial communities ( Peiffer et al, 2013 ; Yang et al, 2019 ; Chen et al, 2020 ; Wang et al, 2020 ). Our increasing awareness of the influences of soil-feature changes on the microbiome has resulted in an emerging urgency to elevate the suppressing effect of soil microbiota against phytopathogens by managing the soil properties.…”
Section: Interactions Of Microbial Communities With Plants and Soilmentioning
confidence: 99%
“…Studies on the contribution of microbial communities to N‐cycling in crop production were conducted in either simplified conventional crop rotations or intercropping systems (Zhao et al ., 2017; Yang et al ., 2019) and only examined the microbial genes of bulk soil (Bakker et al ., 2013; Wu et al ., 2017). Most reports are restricted to a single functional group of microorganisms or to one step of the N‐cycle (Wittorf et al ., 2018) and are based on DNA analyses (Yang et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%